Trabalho e ritual: uma etnografia dos imigrantes e refugiados muçulmanos que realizam o abate halal nos frigoríficos do oeste catarinense - Lopez, Gabriel Angel Jimene (Universidade Federal de São Carlos, 2019)
This dissertation adresses the incorporation of Muslim immigrants and refugees in slaughterhouses to work in the Muslim religious slaughter known as halal. Through field research conducted with Muslim bleeders working at a Brasil Foods (BRF) plant located in the city of Chapecó-SC, I examine the process in which these people are incorporated in halal slaughter lines, as well as how, from their perspectives, this slaughter is practiced inside these slaughterhouses. Addressing the way slaughterhouses lure Muslim immigrants and refugees to work in the halal bleed, I point to a set of questions concerning the precarious conditions that characterize the lives of these workers in the slaughterhouses, as well as the ritual aspects that revolve around the slaughter. Because it is a religious slaughter practiced on a large scale by the meat industry, the research is therefore an interface in which I discuss migration, religion and work.
Trabajo y ritual: etnografia dos imigrantes y refugiados musulmanos que realizan el abate halal en los frigorificos del oeste catarinense
Work and ritual : etnography of immigrants and refugees muslims performing halal slaughter in west of Santa Catarina Brazil
Keywords: Migração; Refúgio; Frigoríficos; Abate; Halal; Ritual; Trabalho; Mercado; Migration; Refuge; Refrigerators; Slaughter; Labor; Market; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA